Strategi Pengembangan Objek Wisata Kolam Air Panas Negeri Tulehu Kabupaten Maluku Tengah - Louise Sitaniapessy; Gilbert Alvin Rumalatu (P3M Politeknik Negeri Ambon, 2024)
This study aims to develop a Strategy Developing Attraction Hot Springs in tulehu, Maluku Regency Middle Of Moluccas. This research uses qualitative descriptive research with survey method. Collecting data using observation, interviews and questionnaires. With the SWOT analysis technique, namely Strengths, Weaknes, Opportunities, Threats. The results show that Tulehu has strength in terms of utilizing the existing natural resources, namely the Tulehu Hot Springs Tourism Object. While the weaknesses are in terms of inadequate infrastructure, lack of budget and inexperienced management of human resources for improving the Tulehu Hot Springs Tourism Object. The opportunity for the Tulehu Hot Springs Tourism Object is to open up employment opportunities for the surrounding community. The lack of facilities and infrastructure is a threat so that it affects visiting tourists and the surrounding community will lose jobs. Suggestions for this research are: (1) Optimizing the use of natural resources, (2) Submission of a budget and in collaboration with the Department of Tourism, Youth and Sports, (3) Provide employment opportunities for the community around the Tulehu Hot Springs Tourism Object, (4) Improve Facilities that are less than optimal.Keywords : Strategy, Attraction